GIS Techniques for the Tsunami Hazard Mapping and Identification of the Evacuation Sites; A Case Study in Devinuwra Area, Southern Sri Lanka - Piyadasa, Ranjana U. K.; Weerasinghe, K.D.N; Chandana, P.G (My University, 2009)
A pilot study was conducted in Devinuwara area Southern Sri Lanka which underwent the Tsunami tragedy in December 2004. The objective of the study was to identify the inundated locations and the magnitude of the damage caused by the 2004 Tsunami wave, to project vulnerable areas in case of a future disaster of the same magnitude or more, and to locate safer areas for the establishment of the evacuation sites. A field survey was conducted through a structured questioner to collect the data on Tsunami impact in the area. GPS coordinates were collected to locate them on a digital elevation map. Levels of the submergence due to 2004 tsunami in the inundated areas were demarcated using GIS techniques. In the investigated areas, the flooded area was demarcated as 86,011 sq meters and the average distance covered by the wave inside the land as 90 meters with a maximum of 530m. The appropriate evacuation sites were identified in the outer skirt of the Tsunami hazard zone, considering the factors of road accessibility, availability of common places, such as temples, schools in coordination with the disaster management center and other stake holder institutions. Accordingly Wawwa temple and Galgane Temple were identified as primary and the Principal evacuation sites respectively. Principle evacuation site was identified after considering the factors such as elevation of the site, accessibility through roads and air, sufficient shelter and space, availability of clean water resources, uninterrupted communication facilities in case of severe damages to the systems etc to meet the needs of a large crowd.